Meeting the Abled? /Disabled? Self When Researching the Lives of Disabled Women - Leslie Broun; Lous Heshusius (Disability Studies Quarterly, 2004)
Offered is a reprocessing of the methodological decisions made in a graduate student's (first author) thesis, tracing her slowly evolving journey through qualitative possibilities in methodology, coming to understand that a choice for a particular methodology is actually a choice for a particular other/self relation. At a still deeper level, this process led to the sudden and painful realization that the needs, fears, and desires of the (often conflicting and shifting) self informs the contours of the other/self relation and thus limits what dares to be gained from the research process. This journey played itself out within a focus on the educational and career achievements of disabled women with the first author including herself as a participant. While the inclusion of herself seemed a natural thing to do, it forged in the end a major, painful and unforeseen confrontation between her imagined 'normal' self she had habituated herself to believe in, and her limping disabled self as she appeared to the world (and at a 'realistic' level through the world's eyes also to herself). Questions are raised about the ongoing upset that occurs when a researcher/participant honestly confronts the configuration of the self in the research process.